2018
DOI: 10.1155/2018/2491652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Normal and Shear Interaction Stiffnesses on Three‐Dimensional Viscoplastic Creep Behaviour of a CFR Dam

Abstract: Rockfill materials and foundation continuously interact with each other during lifetime of the rockfill dams. This interaction condition alters the viscoplastic behaviour of these dams in time. For this reason, examination of the time-dependent viscoplastic interaction analyses is vital important for monitoring and evaluating of the future and safety of the rockfill dams. In this study, it is observed how the time-dependent displacement and stress behaviour of a concrete-faced rockfill (CFR) dam change by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Tanks to the interface elements, a realistic interaction condition is provided between the discrete surfaces. Te numerical values of the interface elements in the normal and shear directions defned between the discrete surfaces are 10 8 Pa/m [40]. Interface elements defned between discrete surfaces are shown in Figure 3.…”
Section: 3d Finite-difference Modelling Of Ermenek Dammentioning
confidence: 99%
“…Tanks to the interface elements, a realistic interaction condition is provided between the discrete surfaces. Te numerical values of the interface elements in the normal and shear directions defned between the discrete surfaces are 10 8 Pa/m [40]. Interface elements defned between discrete surfaces are shown in Figure 3.…”
Section: 3d Finite-difference Modelling Of Ermenek Dammentioning
confidence: 99%
“…Thanks to these interaction elements, important information about the interaction problems of clay core rockfill dams have been presented. The value of the interaction elements defined between the discrete surfaces is 10 8 Pa/m [27]. Then, the Mohr-Coulomb material model was defined for the clay core, rockfill, and foundation parts of the dam.…”
Section: Three-dimensional Modelling Of Kozlu Dammentioning
confidence: 99%
“…For this purpose, Boyabat CG dam that is one of the biggest concrete gravity dams in Turkey is selected as a numerical application. Karalar and Çavuşli [15] studies observed how the time-dependent displacement and stress behavior of a concrete-faced rockfill (CFR) dam change by the effect of the normal and shear interaction spring stiffness parameters. Ilısu Dam that is the longest concrete-faced rockfill dam in the world now and has been completed in the year 2017 is selected for the threedimensional (3D) creep analyses.…”
Section: Introductionmentioning
confidence: 99%